Prevalence of ExoY Activity in Pseudomonas aeruginosa Reference Panel Strains and Impact on Cytotoxicity in Epithelial Cells - Silistre, Hazel; Raoux-Barbot, Dorothée; Mancinelli, Federica; Sangouard, Flora; Dupin, Alice; Belyy, Alexander; Deruelle, Vincent; Renault, Louis; Ladant, Daniel; Touqui, Lhousseine; Mechold, Undine (Frontiers in Microbiology, 2021)
ExoY is among the effectors that are injected by the type III secretion system (T3SS) of Pseudomonas aeruginosa into host cells. Inside eukaryotic cells, ExoY interacts with F-actin which stimulates its potent nucleotidyl cyclase activity to produce cyclic nucleotide monophosphates (cNMPs). ExoY has a broad substrate specificity with GTP as a preferential substrate in vitro. How ExoY contributes to the virulence of P. aeruginosa remains largely unknown. Here, we examined the prevalence of active ExoY among strains from the international P. aeruginosa reference panel, a collection of strains that includes environmental and clinical isolates, commonly used laboratory strains and sequential clonal isolates from cystic fibrosis (CF) patients and thus represents the large diversity of this bacterial species. The ability to secrete active ExoY was determined by measuring the F-actin stimulated guanylate cyclase (GC) activity in bacterial culture supernatants. We found an overall ExoY activity prevalence of about 60 % among the 40 examined strains with no significant difference between CF and non-CF isolates. In parallel, we used cellular infection models of human lung epithelial cells to compare the cytotoxic effects of isogenic reference strains expressing active ExoY or lacking the exoY gene. We found that P. aeruginosa strains lacking ExoY were in fact more cytotoxic to the epithelial cells than those secreting active ExoY. This suggests that under certain conditions, ExoY might partly alleviate the cytotoxic effects of other virulence factors of P. aeruginosa.